Numerical study on photovoltaic thermal phase change material system in hot climatic conditions. (5th June 2023) - Bhakre, Someshwar S.; Sawarkar, Pravin D.; Kalamkar, Vilas R.
Highlights: Performance of PVT/PCM system is compared with PV/PCM system numerically. The optimized WCT for the PVT/PCM system was found to be 30 mm. Maximum average temperature drop of 5.88% was obtained at 30° system orientation. PVT/PCM system electrical efficiency increases by 14.93% compared to PV/PCM system. PVT/PCM system at all system orientations performs better than PV/PCM system. Abstract: High operating temperature of photovoltaic (PV) panels hinder electrical and thermal efficiency, leading to a decrease in performance. To address this issue, researchers have explored various cooling techniques. Phase change materials (PCMs) can be seen as a promising solution to this problem However, the limitations of the PV/PCM system is that, the continuous increase in PCM temperature after melting and the inability to use the heat stored in the PCM. These limitations can be overcome by using a simplified passive water-based PVT/PCM system. In the present study, two separate containers, one filled with PCM and the other with water are used. They are integrated with a PV panel on the backside. Initially, a constant PCM thickness of 50 mm and water container thicknesses (WCT) of 20 mm, 30 mm, and 40 mm were considered to determine a suitable WCT for the proposed PVT/PCM system and the performance was investigated at 90° system orientation. A 2-D computational model is developed and analyzed using ANSYS FLUENT software to determine suitable WCT with PV/PCM system at different system orientations. The preliminary investigation shows that a WCT of 30 mm is the best arrangement for the proposed PVT/PCM system. As the WCT is increased beyond 30 mm, no significant change has been observed in PCM melt fraction and PV panel temperature. Further investigation shows that an increase in the system orientation from 30° to 90° decreases the average temperature of the photovoltaic (PV) panel and phase change material (PCM). The complete melting of PCM results in an average decrease in PV panel temperature of 5.88% (23 °C) and 1.36% (5 °C) at 30° and 90° system orientation, respectively. This decrease in temperature resulted in an overall increase in average electrical efficiency of 14.93% and 1.35% at 30° and 90° system orientations, respectively.